2004
DOI: 10.1038/sj.cdd.4401418
|View full text |Cite
|
Sign up to set email alerts
|

Physical and functional interaction between BH3-only protein Hrk and mitochondrial pore-forming protein p32

Abstract: Bcl-2 homology domain (BH) 3-only proteins of the proapoptotic Bcl-2 subfamily play a key role as initiators of mitochondria-dependent apoptosis. To date, at least 10 mammalian BH3-only proteins have been identified, and it is now being realized that they have different roles and mechanisms of regulation in the transduction of apoptotic signals to mitochondria. Hrk/DP5 is one of the mammalian BH3-only proteins implicated in a variety of physiological and pathological apoptosis, yet the molecular mechanism invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 41 publications
(59 reference statements)
2
67
1
Order By: Relevance
“…Previous studies have shown that silencing of p32 reduced cisplatin-, harakiri-, and p14ARF-p16INK4a locusinduced apoptosis (21,22,25). Similarly, we found that p32 silencing conferred protection against UV-induced apoptosis.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous studies have shown that silencing of p32 reduced cisplatin-, harakiri-, and p14ARF-p16INK4a locusinduced apoptosis (21,22,25). Similarly, we found that p32 silencing conferred protection against UV-induced apoptosis.…”
Section: Discussionsupporting
confidence: 67%
“…Reducing the levels of p32 in mammalian cells has been shown to make them more resistant to apoptosis (21,22), suggesting that p32 has a proapoptotic activity. Consistent with these data, when p32 levels were reduced using siRNA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The dominant theory is that Hrk would inhibit the antiapoptotic function of other Bcl-2 family member by heterodimerizing with them. However, a homotetrameric protein, p32, was recently isolated in a two-hybrid screen by its ability to interact with Hrk (24). Hrk-mediated apoptosis requires tetrameric p32 to form a channel in the mitochondria membrane and destabilize the function of this organelle.…”
Section: Resultsmentioning
confidence: 99%
“…Although p32 can be existed in multicellular compartments, it is predominantly targeted to mitochondria because of the mitochondrial targeting sequence contained in the 73N‐terminal amino acids 25. Functional studies have shown that p32 is required for the induction of mitochondria‐dependent cell death26, 27 and for the metabolic shift between oxidative phosphorylation and aerobic glycolysis 28. Moreover, the crystal structure of p32 has been determined and indicates that p32 can form a pore‐like homotrimer and may serve as a high‐capacity divalent cation storage protein 29.…”
mentioning
confidence: 99%